Women Entrepreneurship in Small and Medium Enterprises in North Macedonia - Atixhe Maksuti; Ali Maksuti (Research Parks Publishers, 2022)
The entrepreneur is one of the most important and essential input used in the production and services process and have effect in growth of economy of the country or nation. So and in microeconomic aspect, entrepreneurs have an important role in building and creating a new companies. They also are contributors in most of the time promoting the creation of new era of business and incorporation new technology, new management in the markets. So , in this case we can say that entrepreneur is part of economic development , open new opportunities for employment and increase other economic sectors in an open economy. But, and in another hand, the women also play an important role in the social and economic development of any country. Two main factors that were presented in process of being the women in transition economy and her contribution in social and economic development, firs is the traditional role and the second countries like North Macedonia that is part of developing countries , where all the process of transition was in hand only of politicians. But, after time things has changed and last years women is important part of the increasing entrepreneur and is part of small and medium businesses.Expect the political and economic transition of North Macedonia, in our country is presented and transition from traditional to modern function of the society that open doors to women to be part of contribution in economic growth. Last years, North Macedonia has changed the percentage of women that are part of business, all details offer us that last 10 years the percentage has increased for 6%. About this, have worked in this research paper to present that women are part in every sector of economy, are part of joint venture, are part of NGO-s that contribute to establish mindset of entrepreneur , are part of foundations that contribute for increasing the efficient of entrepreneur etc.